The metabolite 5′-methylthioadenosine signals through the adenosine receptor A2B in melanoma - Limm, Katharina; Wallner, Susanne; Milenkovi, Vladimir M.; Wetzel, Christian H.; Bosserhoff, Anja Katrin (European Journal of Cancer, 2014)
Several recent studies have shown evidence supporting the general knowledge that tumour cells exhibit changes in metabolism. It is becoming increasingly important to understand how these metabolic changes in tumour cells promote carcinogenesis and disease progression. We recently discovered a lack of methylthioadenosine phosphorylase (MTAP) expression in melanoma, which resulted in an accumulation of the metabolite 5′-methylthioadenosine (MTA) in melanoma cells and in the extracellular environment. MTA was shown to affect cell proliferation of surrounding stroma cells and cell invasiveness and the activation of the transcription factor activator protein-1 (AP-1) in melanoma cells. In this study, we addressed the regulation of cellular signalling by extracellular MTA accumulation. By focusing on putative receptors that could modulate MTA signalling, we identified the adenosine receptor ADORA2B as an important candidate. Knockdown experiments and the use of specific agonists and antagonists confirmed a link between MTA and AP-1 signalling through the ADORA2B receptor. Interestingly, stimulation of the cells with MTA did not result in activation of the classical cyclic adenosine monophosphate (cAMP) signalling cascades or in Ca2+-dependent signalling. We instead showed protein kinase C (PKC) signalling to be involved in MTA-mediated AP-1 activation. In summary, we identified ADORA2B to be the specific receptor and signalling pathway for the metabolite MTA. These findings may influence the use of MTA in a therapeutic manner.
CRIS-Team Scopus Importer:2022-08-05
Keywords: 5′-Methylthioadenosine; Adenosine receptor A2B; AP-1-trascription factor; CREB-1 pathway; MAPK/ERK - PKC signalling; Melanoma